Ecological and Pharmacological Activities of Antarctic Marine Natural Products - Avila, Conxita (Planta Medica, 2016)
Antarctic benthic communities are regulated by abundant interactions of different types among organisms, such as predation, competition, etc. Predators are usually sea stars, with omnivorous habits, as well as other invertebrates. Against this strong predation pressure, many organisms have developed all sorts of defensive strategies, including chemical defenses. Natural products are thus quite common in Antarctic organisms with an important ecological and pharmacological potential. In this paper, the chemical defenses of the Antarctic organisms studied during the ECOQUIM and ACTIQUIM projects, as well as their pharmacological potential, are reviewed. For the ecological defenses, predation against the sea star Odontaster validus is analyzed and evaluated along depth gradients as well as considering the lifestyle of the organisms. For the pharmacological activity, the anticancer, anti-inflammatory, and antibacterial activities tested are evaluated here. Very often, only crude extracts or fractions have been tested so far, and therefore, the natural products responsible for such activities remain yet to be identified. Even if the sampling efforts are not uniform along depth, most ecologically active organisms are found between 200 and 500 m depth. Also, from the samples studied, about four times more sessile organisms possess chemical defenses against the sea star than the vagile ones; these represent 50 % of sessile organisms and 35 % of the vagile ones, out of the total tested, being active. Pharmacological activity has not been tested uniformly in all groups, but the results show that relevant activity is found in different phyla, especially in Porifera, Cnidaria, Bryozoa, and Tunicata, but also in others. No relationship between depth and pharmacological activity can be established with the samples tested so far. More studies are needed in order to better understand the ecological relationships among Antarctic invertebrates mediated by natural products and to fully explore their pharmacological potential.
Keywords: chemical ecology; marine benthos; antarctic invertebrates; chemical defense; cytotoxicity; anti-inflammatory activity; antibacterial activity